100 Multi-disciplinary Clinic: Next Step In "heart Team" Approach For Tavi. (31st May 2014) - Chelliah, Raj; Showkathali, Refai; Brickham, Beth; Dworakowski, Rafal; Alcock, Emma; Deshpande, Ranjit; Wendler, Olaf; MacCarthy, Philip; Byrne, Jonathan
Abstract : Introduction: The "Heart team" approach is considered to be the most appropriate method for assessing patients for consideration of Transcatheter Aortic Valve Implantation (TAVI) in severe aortic stenosis. Thus far, the approach has involved the discussion of patients in a multi-disciplinary meeting (MDM) involving interventional cardiologists, imaging specialists, surgeons, anaesthetists and elderly care physicians. The disadvantage of this approach is that the patients are often reviewed remotely by a single specialist. We have developed a unique model of multi-disciplinary clinic (MDC) for assessing patients for TAVI; in this model the patients are reviewed by an interventional cardiologist, cardiac surgeon and anaesthetist in the same clinic. We report the first 8 months data of patients reviewed in this clinic and the outcomes. Methods: The TAVI MDC at King's College hospital has run twice a month since January 2013. Data for all patients who attended this clinic were collected and analysed. For those who attended the clinic more than once, the decision made during the first visit was included for analysis. We compared this with that taken from MDM patient discussions (n = 71) undertaken in the 8 months prior to the inception of the clinic. Results: During the study period, 64 appointment slots were made in the clinic. 48 patients (83 ± 6 yrs, 22 female) were reviewed in the clinic 57 times (7 patients seen twice, one patient seen three times). The outcome of clinic decisions for these patients is shown in Figure 1 . This was compared with the outcome for patients discussed in the preceding 8 months. (Table 1 )TAVI work-up was completed prior to clinic appointment in 15 patients (31.3%) compared to 62 patients (87.3%, p < 0.0001) in the MDM group. A total of 13 patients in the MDC group and 28 patients in the MDM group finally underwent TAVI. In those who finally underwent TAVI, the time interval between clinic/discussion to TAVI was shorter in the MDC group when compared to the MDM group (median 54, IQR 36–88 days vs 130, 64–171 days, p = 0.01). The TAVI 'turn-down' rate was also higher when patients were reviewed in MDC when compared to MDM discussion (35.4% vs 16.9%, p = 0.03). Conclusion: This is the first report of the live "Heart team" clinic data. TAVI decline rate was higher when patients were seen earlier in the process by the team, thereby avoiding unnecessary costs of TAVI work-up investigations. Patients underwent TAVI quicker when seen and accepted in the MDC. This model offers the potential for a more effective method of multidisciplinary assessment, but does require significant resource allocation.